Sizing AC/DC building distribution network : part II (renewable energy (PV) and energy storage for system design) - Li, Fa Li (Nanyang Technological University, 2020)
World has become more conscious about environment and changes occurring in climate. We are giving more attention to the effects of the technological and industrial revolution on the ecology and the human health that result in intense research towards renewable energy. Solar energy remains as the most promising and efficient renewable energy source for Singapore when generating electricity and it is widely use in various sectors such as industrial usage and residential usage. This project addresses the sizing of AC/DC building distribution network, which mainly focus on the solar Photovoltaic (PV) system and energy storage system for a residential building in Singapore. The aim of this project is to investigate solar PV system for a residential building in Singapore, which includes battery energy storage system for storing solar energy produce from the solar PV system. Besides, calculation of solar energy produce from solar panel will be based on area and weather condition of the residential area. In addition, sizing and selection of various components of solar PV system will be carry out base on the load demand profile of a residential building. This includes the calculation of AC and DC load demand characteristic of the residential building and the configuration of the solar PV system with battery storage will be prescribe.